Hak Dan Kewajiban Warga Negara Dalam Kasus Pembangunan Kawasan Industri Di Pulau Rempang - Rizkya Ramadani; Siti Hardianti; Syafrilia Yolanda (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This research discusses the rights and obligations of citizens in the case of industrial area development on Rempang Island. Rempang Island in Riau Archipelago Province, Indonesia, has become the center of attention because of plans to build the Rempang Eco City by PT Makmur Elok Graha in collaboration with Xinyi International Investment Limited from China. This project worth USD 11.5 billion will transform the island into an industrial, service and tourism area, but faces strong resistance from the 16 traditional villages that have been settled since 1834. This research uses library research and a qualitative approach. This means that this research was carried out using data collection methods. This research aims to explain what rights and obligations Indonesian citizens must have so that they can improve their character and responsibility and to examine this conflict from the perspective of human rights and the impact of development on local communities. This conflict is considered a violation of human rights, especially regarding forced evictions, the right to justice and the right to freedom of expression. The government is expected to fulfill its obligation to respect, protect and fulfill the rights of affected communities by providing fair relocation solutions and adequate compensation.